PERLINDUNGAN HUKUM TENAGA KERJA BONGKAR MUAT (TKBM) KOPERASI TKBM KMB NUNULAI KABUPATEN KONAWE BERDASAR HUKUM PENGANGKUTAN - Jabalnur, Jabalnur; Saputra, Idris; Handrawan, Handrawan; Ukkas, Jumiat; Yusuf, Haris (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
The port has an important role, for example in trade. Merchant ships that load or deliver goods will stop at the port, this certainly requires adequate human resources and support these activities. In the port, the most visible activity besides transporting passengers is the activity of unloading or loading goods, which means that business entities in the field of sea transportation are needed, in order to be able to encourage the running of loading and unloading activities properly and not cause losses. Loading and unloading activities are the activities of transferring transportation goods both from the transport vessel to the port / dock or vice versa (regulated in Minister of Transportation Regulation Number 152 of 2016 concerning the Implementation and Operation of Loading and Unloading from and to Ships). Article 1 of Ministerial Regulation Number 152 of 2016 concerning the Implementation and Business of Loading and Unloading from and to Ships, states that at the Port which has an influence on the smooth transportation process is the loading and unloading of goods. The services to carry out this activity are carried out by a company as a legal entity called a Loading and Unloading Company or PBM, and cannot be carried out by individual services, one of which is TKBM KMB Nunulai which is engaged in the provision of loading and unloading labor services at the port of Morosi where in the initial survey the implementation is still far from the provisions of what is regulated in transportation and labor law.